Does the EU ETS cause carbon leakage in European manufacturing? - Helene Naegele; Aleksandar Zaklan (Journal of Environmental Economics and Management, 2019)
Carbon leakage is of interest in both academic and policy debates about the effectiveness of unilateral climate policy, especially in Europe, where the EU Emissions Trading System (EU ETS) affects many traded sectors. We review how the literature identifies leakage and the pollution haven effect. We then evaluate whether EU ETS emission costs caused carbon leakage in European manufacturing, using trade flows in embodied carbon and value from the Global Trade Analysis Project (GTAP). We find no evidence that the EU ETS caused carbon leakage.
Keywords: Q56; F18; Q58; Q54; 330; Carbon leakage; Pollution haven; EU ETS; Cap-and-trade; CO emissions; Policy evaluation